METHOD FOR DETECTING, QUANTIFYING AND CHARACTERIZING BRETTANOMYCES SPP YEASTS AND OTHER YEASTS CONTAINED IN AN ORGANIC LIQUID SUBSTRATE CONTAINING FERMENTABLE SUGARS - DUBERNET, Matthieu (2025)
The invention relates to a method for detecting, quantifying and differentiating by flow cytometry Brettanomyces spp yeast cells contained in an organic liquid substrate which contains fermentable sugars, whereby a sample of said substrate is taken, optionally diluted, at least a first fluorochrome capable of binding to the DNA of dead and/or live cells is added to said optionally diluted substrate, said sample is irradiated so as to obtain the fluorescence emission of said first fluorochrome and said sample is also irradiated so as to obtain a fluorescence emission of said sample at 670 nm, a biparametric histogram is plotted giving for each point the fluorescence intensity due to the first fluorochrome coupled with the fluorescence intensity emitted at 670 nm, at least a first point cloud is thus obtained corresponding to a greater fluorescence intensity emitted and detected at 670 nm than that detected for the other points, it is inferred therefrom that the points of said first cloud correspond to the Brettanomyces spp cells.